Evaluation of different pruning solutions for superhigh density olive orchards - Dias, António F. (2020)
In the super high density olive orchards, manual pruning is the current practice used by olive growers. This option requires a large amount of labour. Although disc saw pruning machine allow high work rate, it would be necessary to evaluate the influence of the use of the pruning machine in olive yield in order to establish a pruning strategy. In 2015 a trial was established in a commercial orchard of Arbequina cultivar. The orchard was planted, in the year of 2006, according to 3,75 meters between rows and 1,35 meters between trees in the row. The trees were trained according to the central leader system. In this trial, in a randomised complete block with three replications, three treatments (T1; T2; T3) are being compared leading to 9 plots with 480 trees per plot. The treatments under study are: T1 - manual pruning using chain saws; T2 - mechanical pruning + manual pruning; topping the canopy parallel to the ground and hedging on the two sides of the canopy in 2015; topping the canopy parallel to the ground twice in 2016 (winter pruning and summer pruning); manual pruning in the winter of 2017 and topping the canopy parallel to the ground in the summer of 2017; hedging the two sides of the canopy in the winter of 2018 and topping the canopy parallel to the ground in the summer of 2018; T3 – mechanical pruning + manual pruning; hedging on the East side of the canopy in 2015 with an oblique cut; manual pruning in West side of the canopy in 2016; manual pruning in the East side of canopy in 2017 and hedging on the West side of the canopy in 2018 with an oblique cut. The topping parallel to the ground in the summer could be useful to control suckers in the top of the canopy. Significant differences in olive yield between years were found: Treatment 2 obtained more regularity on olive yield among years. More years of field work are essential to define the better pruning strategy.